Acuminata condyloma extragenital associated to intertrigo: case report - Reis, Helena Lucia B. (2008)
Introduction: the human papillomavirus (HPV) is a DNA virus that can infect skin and mucosa, already described in more than 100 different types, being 45 of those considered to be sexually transmitted. Objective: report the extra-genital case of condyloma acuminata, facilitated by the presence of intertrigo. Method: report of a case of female patient presenting extensive condylomatous lesions associated to intertrigo in hypogastric region. Results: a 46-year-old female patient assisted in the DST/AIDS Clinic of the Gynecology Sector at Santa Casa de Misericórdia from Vitória in 2007, presenting extensive condylomatous lesions associated to intertrigo in hypogastric region above the Pfannestiel scar and small compatible vulvar ver rucosa lesions suggestive of condyloma. Surgical excision was made in the abdomen lesion which evidenced condyloma acuminatum and chemical cauterization of vulvar warts. Tests for sexually transmitted diseases were requested, all of them were normal, including oncotic cytology, colposcopy and fast test for gonococcus and chlamydia. Conclusion: local humidity and heat provoked by abdomen in apron with concurrence of area of intertri go could justify the presence of condyloma acuminatum in this region.